IMPLEMENTASI PEMBELAJARAN BERBASIS SPIRITUAL DI MASA PANDEMI COVID-19 MELALUI VIRTUAL CLASSROOM DI SEKOLAH DASAR ISLAM KHALIFAH KOTA SERANG - Lelianasari; Ujang Jamaludin; Reksa Adya Pribadi (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2022)
Spiritual learning is one of the real efforts toward the implementation of character education which is a government program. This article provides an overview of the implementation on spiritualbased learning in the Covid-19 pandemic era through virtual classrooms at the Khalifah Islamic Elementary School in Serang City for fourth-grade students. Spiritual-based learning at SDI Khalifah was pursued in the form of worship and strengthening activities carried out by teachers during the learning process. The research method used in this article was a qualitative method of case study design through triangular data collection techniques such as interviews, observations, and documentation by using the Miles and Huberman data analysis model, namely the process of data collection, data reduction, and data presentation or drawing conclusions. The results showed that spiritual-based learning activities that took place at SDI Khalifah were worship activities and commendable behavior that took place during learning in the form of habituation and delivered orally. Spiritual-based learning, thus, was pursued by the teacher through a virtual classroom of the zoom cloud meeting type.